Occurrence, data-based modelling, and risk assessment of emerging contaminants in an alluvial aquifer polluted by river recharge. (1st January 2023) - Labad, Francesc; Ginebreda, Antoni; Criollo, Rotman; Vázquez-Suñé, Enric; Pérez, Sandra; Jurado, Anna
Abstract: This research presents the occurrence and fate of 121 contaminants of emerging concern (CECs) in an urban aquifer polluted by river recharge through a data-base modelling. Afterwards, risk quotients (RQs) are computed to determine the risk posed by CECs to human health. To this end, groundwater and river water samples were collected in four campaigns conducted from February to May 2021. Results show that 46 CECs are ubiquitous in groundwater and their concentrations vary several orders of magnitude, ranging from below the limit of quantification to 44.5·10 3  ng/L for iopamidol. Transformation products (TPs) are usually detected at lower concentrations than those of the parent substances but there are some exceptions (i.e., fipronil sulphide, fipronil sulfone and O-desmethylvenlafaxine). River concentrations are higher than those detected in groundwater for some CECs, indicating the occurrence of natural attenuation processes when river water infiltrates the aquifer. A data-based advection-reaction modelling is proposed and tested for ca. 40 substances with detection frequencies higher than 90%. It provides useful quantitative information regarding the dynamic behaviour of the variables monitored, expressed in terms of characteristic length, entropy and synchronized state contribution. Finally, risk quotients (RQs) are used to assess the human health risk posed by the ubiquitous CECs in groundwater. Most CECs do not pose any risk to the different life stages considered, as the RQs evaluated are lower than 0.01. However, the pharmaceuticals valsartan and its TP valsartan acid show RQs higher than 1, indicating that these substances might be harmful to human beings. Graphical abstract: Image 1 Highlights: Contaminants of emerging concern (CECs) might deteriorate urban groundwater quality. Some CECs are naturally attenuated in groundwater under nitrate-reducing conditions. The advection-reaction model allows understanding their behaviour in groundwater. Most CECs do not pose any risk to human health at detected concentrations.